The Chinese Friends in Thailand - Tonsiengsom , Surangsri (Journal of Sinology (วารสารจีนวิทยา), 2007)
Among East Asian countries such as China, Japan, and Korea, China is a country which had the longest political, economic, and social relationships with Thailand. From the Sukhothai period, some Chinese had started to immigrate to Thailand. Due to Chinese internal and external problems of the number of Chinese immigrated kept increasing especially in the Rattanakosin period. Moreover, Thai society also encourages Chinese to come to Thailand. This paper will study some of them who became Thai nobles. In order to understand this picture, this paper was divided into four topics; firstly, the coming of Chinese in Thailand; second, the uniqueness of the Thai society; thirdly, the Chinese who received Thai royal titles and fourthly, conclusion.